We will eat disgusting foods together – Evidence of the normative basis of Western entomophagy-disgust from an insect tasting. (March 2019) - Jensen, Niels Holm; Lieberoth, Andreas
Highlights: Perceived infectability does not predict insect-disgust or WTE insects. Trait-level pathogen disgust sensitivity does not predict insect-disgust or WTE insects. Perceived social norms predict insect eating behavior. Abstract: Insects are a highly sustainable and nutritious source of protein, and, thus, incorporating insects in to Western food culture is one way to address major global challenges like global warming and deforestation. Consumer studies show, however, that Westerners' willingness to eat insect-containing food is low. One formidable barrier is the perception that insects are disgusting, and it is generally believed that this insect-disgust is driven by a fear of contamination and disease. Another barrier is the lack of social norms related to entomophagy in the West. In the present study, we tested effects of fear of contamination and perceived social eating norm with a survey and a tasting session administered to a Danish college sample ( N  = 189). Correlation analyses and multivariate regression analyses revealed that selfreported trait-level Pathogen Disgust and Perceived Infectability did not consistently predict insect eating disgust, willingness to eat insects, or actual insect tasting behavior in the tasting session. In contrast, perceived insect eating norm emerged as a significant predictor of insect tasting behavior. These findings suggest that perceived social norms play a substantial role in Westerners' (un)willingness to eat insects. The result gives reason for optimism for aspirations of introducing insects in Western food diet and point to avenues for harnessing social norms in marketing efforts.